THE EFFECTIVENESS OF OPERATIONAL MANAGEMENT IN OVERCOMING PAYROLL DELAYS AT PT TRI ARSA MANDIRI - Muh Farhan Firman; Suriyanti; Mahfudnurnajamuddin (STMIK Indonesia Banda Aceh, 2026)
This study aims to analyze the effectiveness of operational management in overcoming payroll delays at PT Tri Arsa Mandiri, a shipping agency company. Methodology / approach: The research uses a descriptive qualitative approach with a case study method. Data were collected through observation, semi-structured interviews with 8 informants (5 employees, 2 finance staff, and 1 operations manager), and document analysis of payroll policies and reports for the 2022-2023 period. Data were analyzed thematically to identify causal factors and formulate improvements. Findings: The study found that the manual payroll system causes process inefficiency, low accuracy, and delays in salary distribution. Key inhibiting factors include limited technological resources, complexity of tax calculations, lack of standardized procedures, and high dependence on specific individuals in the verification process. The proposed solution is the implementation of a computerized payroll system, development of clear Standard Operating Procedures (SOP), and training for finance staff. Originality / value: This research provides practical insights into operational management improvements in payroll systems within the context of Indonesian shipping agency companies, which have not been widely studied. The recommendations are contextual and can be directly applied by the company. Practical implications: The implementation of technology-based solutions and procedural standardization is expected to improve operational efficiency, tax compliance, and employee productivity.